PERUBAHAN STRATEGI BERTAHAN HIDUP MANUSIA PRASEJARAH: SISTEM PENGUMPULAN DAN PRODUKSI PANGAN - Elsha Putriany Br Girsang; Mhd Arif Parluhutan Sitompul; Angel Sinambela; Yeza Pebina Kaban; Nahot Andika Nainggolan; Flores Tanjung (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the transformation of prehistoric human food systems from foraging to food production through a literature review. The study's findings indicate that this shift was influenced by climatic factors, an increase in population, and advances in human cognitive abilities, which ultimately drove the domestication of plants and animals as well as the emergence of sedentary lifestyles.